Anton Chekov's The Bet: An Existentialist View - Salman Hamid Khan; Dr. Abdul Hamid Khan; Farishta Hamid Khan (University of Chitral Journal of Linguistics and Literature, 2023)
This paper employs the framework of Fredric Nietzsche, as theorized in Thus Spoke Zarathustra, to interpret Chekhov's story The Bet (2013). The story is about a young lawyer who enters a contract to bargain his youthful fifteen years in solitary confinement to win two million from a rich banker. The Bet (2013) explores whether capital punishment is humane or life imprisonment is a better option for crime and punishment. The study is qualitative, and through textual analysis, findings have been reached using Nietzsche's existential theoretical lens. The study finds that the lawyer suffers imprisonment but leaves before its termination as he has discovered all meanings of life are mere illusions. The study concludes that Chekhov scans the normative behaviors of people, in this case, the Banker and lawyer, and proves to be a sad reflection on the human condition.